Effect of low-intensity aerobic exercise using a cycle-ergometer on insomnia level and quality of life in breast cancer patients undergoing chemotherapy - Difitasari Cipta perdana; Indrayuni Lukitra Wardhani; Desak Agung Gede Suprabawati; Damayanti Tinduh (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Background: Patients undergoing chemotherapy are two to three times more likely to experience insomnia, with the highest prevalence reported among breast cancer patients. This condition markedly reduces quality of life. This study aimed to assess whether a low-intensity aerobic exercise program using a stationary bicycle could alleviate insomnia and improve patients’ quality of life. Methods: A randomized controlled trial was conducted at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, involving female breast cancer patients undergoing chemotherapy. Participants were assigned to either a treatment group, which performed low-intensity cycling twice weekly for eight weeks, or a control group with no exercise intervention. Changes in insomnia severity and quality of life were assessed using validated questionnaires before and after the intervention. Results: Among the 20 participants who completed the study, the treatment group showed a significant reduction in insomnia severity (p < 0.001) and greater improvements in physical function, symptom management, and overall well-being compared to the control group. Conclusion: Low-intensity aerobic exercise on a cycle ergometer is a safe and effective way to reduce insomnia and improve quality of life in breast cancer patients undergoing chemotherapy.